TikTok Trick: Improving Students’ Pronunciation of Indonesian Migrant Workers Children in Malaysia - Bella Sukma Suwanda; Bambang Harmanto; Ana Maghfiroh; Shohenuddin Shohenuddin (Journal of Languages and Language Teaching, 2024)
Pronunciation is the most important thing that non-native speakers must deal with when learning a foreign language. The purpose of this research is to improve students’ English pronunciation by using TikTok media. The research method was classroom action research with tests at the end of each cycle. It was conducted in grades IV at Sanggar Bimbingan Sentul, Kuala Lumpur Malaysia, for the 2022 academic year. This classroom action research consisted of two cycles with four stages that were planning, action, observation, and reflection. The learning media used was video taken from the TikTok account @learnenglishwithcamille. The results showed that students’ English pronunciation increased after using TikTok media. This can be seen from the results of observations at cycle 1 reached 45% in the “enough” category, 55% reached the “good” category, and increased at cycle 2 to 40% students in the category “very good”, 45% in the category “good”, and 15% in the category “enough”. In conclusion, TikTok media can improve students’ English, especially in terms of English pronunciation. The implication of the study is that students enjoy learning pronunciation with TikTok media and well improved.